Pemanfaatan Kecerdasan Buatan (Artificial Intelligence) untuk Peningkatan Kualitas Pembelajaran di SMP Negeri 2 Ambon Melalui Pelatihan Guru - Rahangmetan, Delly Angel Patrecia; Leuwol, Ferdinand Salomo; Lasaiba, Mohammad Amin (Jurnal Pengabdian Arumbai, 2025)
The development of Artificial Intelligence (AI) in education presents new opportunities to enhance learning quality. However, in many schools, including SMP Negeri 2 Ambon, its utilization remains limited due to a lack of digital literacy among teachers and infrastructural constraints. This community service program aims to improve teachers' understanding and skills in utilizing AI through hands-on training. The method used in this program involves interactive training, which includes theoretical sessions, practical exercises, and simulations of AI applications in teaching. Evaluation is conducted through observations, interviews, and questionnaires to measure the effectiveness of the training. A total of 15 teachers from various subject areas participated in the program. The training results indicate that 85% of participants experienced an improvement in their understanding of AI and its application in education. Teachers who attended the training began integrating AI into lesson planning, automated assessments, and personalized learning for students. However, the main challenges faced include limited technological infrastructure and the need for ongoing mentoring for teachers struggling to adopt AI. The implications of this program suggest that AI training for teachers can enhance teaching quality and learning efficiency. Therefore, further support is needed in the form of better infrastructure, supportive school policies, and continuous training programs to ensure the optimal and sustainable implementation of AI at SMP Negeri 2 Ambon and other schools.